Geology and metal ore deposits in the Argentine Puna - Gorustovich, Sergio Antonio; Monaldi, Cesar Ruben; Salfity, Jose Antonio (SCS Publisher, 2011)
Fil: Gorustovich, Sergio Antonio. Comisión Nacional de Energía Atómica; Argentina